2005
DOI: 10.1038/sj.eye.6701966
|View full text |Cite
|
Sign up to set email alerts
|

High-volume surgery in developing countries

Abstract: Background Cataract remains the world's leading cause of blindness. In the developing world, many eye clinics provide cataract surgery for only a small proportion of those in need. This is partly because of low demandFcaused by barriers related to awareness, bad services, cost, and distanceFand partly because of deficiencies in the supply of services. This article reviews innovations in cataract surgery in poor countries that are intended to reverse this trend. Conclusions Increasing the number of operations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 27 publications
1
65
0
Order By: Relevance
“…Its success lies in its quick recovery, reduction of post-operative (against-the-rule) astigmatism, costeffectiveness and high success rates [18]. Additionally, it is associated with a lower incidence of fibrinous anterior uveitis and rounder pupils than standard ECCE surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Its success lies in its quick recovery, reduction of post-operative (against-the-rule) astigmatism, costeffectiveness and high success rates [18]. Additionally, it is associated with a lower incidence of fibrinous anterior uveitis and rounder pupils than standard ECCE surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Cost is a major barrier to uptake of CSS in resource-limited economies, including the WA subregion. [13][14][15][16][17] Social marketing of CSS most likely would boost uptake of CSS and raise CSR. This involves creating demand for CSS by getting cataract patients informed about where to get quality, accessible and affordable CSS.…”
Section: Discussionmentioning
confidence: 99%
“…3 A major proportion of total blindness in India (81%) is constituted by cataract blinds. Yorston 4 has suggested that four barriers in limiting access to cataract surgery worldwide: Lack of knowledge, uncertainty over the quality of available services, transportation problems, and concerns over the cost of surgery. The present study was carried out to assess the knowledge, attitude and practices regarding cataract surgery.…”
Section: Introductionmentioning
confidence: 99%